2018
DOI: 10.1177/1756829318794004
|View full text |Cite
|
Sign up to set email alerts
|

Ethics for civil indoor drones: A qualitative analysis

Abstract: Drones face two main concerns: safety and security/privacy. Whilst safety has been broadly studied by literature, less research has been carried out into security/privacy. Moreover, current European regulations on drone flights apply to outdoor drones but not always to their indoor counterparts. However, several industrial sectors have started to use drones for indoor tasks such as surveillance, architecture, emergencies, and communication media. A qualitative study has been conducted in order to explore the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 19 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…In our STEAM project, we have related all of them as we think that STEAM competences are easier to understand for the students. In our Master Programs, we observe that we have still some of them to cover [8], so it would be convenient to complete them through new practices and activities. Specifically, we observed that the cross-sectional competence UPV 5 (Design and project) is not enhanced and it could be related to S (Science).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our STEAM project, we have related all of them as we think that STEAM competences are easier to understand for the students. In our Master Programs, we observe that we have still some of them to cover [8], so it would be convenient to complete them through new practices and activities. Specifically, we observed that the cross-sectional competence UPV 5 (Design and project) is not enhanced and it could be related to S (Science).…”
Section: Discussionmentioning
confidence: 99%
“…Anyway, as all of them presented their works in the classroom, their classmates could see the potential of the tool. We provided also an example [8] to show the possibilities of the software, in this case VosViewer (Figure 4): Finally, the questionnaire was provided and, as we can observe in Table 1, both competences were covered with this activity. To the question "Do you ask yourself own questions around a topic that arouses your curiosity?…”
Section: Students' Surveymentioning
confidence: 99%
“…In our case, during the flight around the person, a visual interaction between the robot and the assisted person is produced. The objective of this work is to analyse how this monitoring path should be in order to elicit the highest degree of safety and comfort feelings in the monitored person, which is an imperative issue for indoor drones [ 31 ]. For this reason, three key parameters, which are detailed below, are proposed.…”
Section: General Description Of the Systemmentioning
confidence: 99%
“…With reference to the section (c), the Regulations introduced a requirement for the establishment of digital harmonised and interoperable national registration systems, in which information regarding the UA and their registered operators should be stored. The national registration systems should be consistent with the EU legislation, considering the matters of security, privacy, personal data protection and environmental protection [10,21].…”
Section: Overview Of Proposed European Legal Regulations In Relation mentioning
confidence: 99%
“…It should be emphasised that the full integration of unmanned and manned aviation will also enable the performance of passenger communication flights, also in the global dimension. This means that there is a need to educate the public opinion that flights without pilots on board are equally safe as in the manned aircraft [21].…”
Section: Societal Issues Of Integration Of Remotely Piloted Aircraft mentioning
confidence: 99%